The Effect of NPK Fertilizer and AM Fungi on the Growth and Yield of Cotton (Gossypium hirsutum L.) var. LRA 5166 - K. Ramakrishnan2, S. Sridevi1* (Recent Research in Science and Technology, 2010)
An experiment was conducted to find out the effect of NPK fertilizer and AM fungi on cotton (Gossypium hirsutum L.) var LRA 5166. The recommended fertilizer schedule of 80:40:40 kg N, P2O5 and K2O was followed for the varieties cotton crop. The growth attributes like plant height, plant fresh and dry weights and yield attributes, like number of sympodial branches, bolls etc., were noticed maximum under increased 100 per cent NPK with AM fungi inoculated plants. The plant height, plant fresh and dry weight and yield of inoculated plants that received 50 per cent NPK/ha was on par with the uninoculated plants supplied with 100 per cent NPK/ha.